Evolution And Its Misinterpretation By The Scientific Community - Muhammad Owais Isaac (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Allah has created the heavens and the earth in stages as he declares in the Holy Quran. It is Allah Who creates, develops and sustains life, and ensures harmony and diversity in all things, living and non-living. The verses from the Quran make it obvious that the conditions required for God’s ultimate creation to exist and survive are only possible if the universe contains matter, energy, water, and other entities as they are. The total measure of these entities cannot be altered, which means the total energy and matter in the universe is constant. These values are actually the result of the fine-tuned universe, where any deviation from it will lead to its instability and hence its extinction. This balance is maintained by the eternal and extremely intelligent being through His commands, and these commands, by observers, are conceived as laws of nature or scientific laws. This universe is solely meant for the trial of the ultimate creation, hence puzzling, brain-teasing, and other sorts of entangled phenomena in the observable universe are inevitable. This kind of nature is intentionally imparted to the universe by God to test mankind (God’s ultimate creation). The definition of biological evolution in modern science is actually an illusion and hence a trial for humans, since God calls this universe by the word